The verdict : a novel - Stone, Nick, 1966- (Pegasus Crime, 2015)
Taking a high-profile murder case that may make his career, Terry Flynt is forced to confront secrets from the past when he discovers that his millionaire client, who is a former friend, brutally betrayed him years earlier.